ANTI DIABETIC EFFECT OF ORAL ADMINISTRATION OF CINNAMON IN WISTAR ALBINO RATS - Kumar, S. S.; Mukkadan,; J. K. (BALI MEDICAL JOURNAL, 2013)
Background: The present study was undertaken with an objective to observe effectiveness of oral administration of cinnamon extract to hyperglycemic induced rats using alloxan. Male and female Wistar Rats were injected with alloxan to induce hyperglycemia. Methods: This is an experimental study to determine whether cinnamon has an ability to combat hyperglycemic rats. Blood glucose was estimated by GOD-PAP method using diagnostic kit supplied by Agappe diagnostics, Maharashtra. Results: The present experimental study provides further evidence that oral administration of Cinnamon extract for 21 days produced a significant decrease in the blood glucose level in the model of alloxan induced diabetes rats. Conclusion: From this study, we can conclude that the oral administration of Cinnamon extracts have beneficial effect on blood glucose levels. However further pharmacological and biochemical investigations will clearly elucidate the mechanism of action and helpful in projecting these plant extracts as a therapeutic target in diabetes research.